Programmed cell death 2 functions as a tumor suppressor in osteosarcoma - Yang, Yuanxun (Int J Clin Exp Pathol, 2015)
Objectives: To investigate the role of programmed cell death 2 (PDCD2) in osteosarcoma (OS), along with correlations between PDCD2 and CD4(+)/CD8(+). Methods: Sprague-Dawley (SD) rats were randomly assigned to control group and OS group. The OS group rats were subjected to induce models of OS by transplantation with UMR106 cells. Peripheral blood was collected to test the percentages of the CD4(+) and CD8(+) cell subsets using flow cytometry (FCM). Western blotting was performed to determine the PDCD2 protein level. The correlations between PDCD2 and CD4(+)/CD8(+) were analyzed by Pearson correlation coefficient. Besides, specific small interfering RNAs (siRNA) against PDCD2 and nonspecific (NS)-siRNA were transfected into UMR106 cells. Cell viability and invasive ability were determined after transfection. Results: CD4(+) cells percentages were significantly decreased in the OS group, while CD8(+) cells were significantly increased (P < 0.05). The PDCD2 protein levels were markedly lower than that in the control group (P < 0.05). Additionally, PDCD2 was positively correlated with CD4(+) (R(2) = 0.66, P < 0.05), but was negatively correlated with CD8(+) (R(2) = -0.94, P < 0.05). Moreover, the cell viability and invasion ability were significantly higher than that in the control group and the NS siRNA group after transfection with PDCD2 siRNA (P < 0.05). Conclusion: These results suggest that PDCD2 is involved in the pathogenesis of OS, and PDCD2 may play an important role in tumor suppression. These mechanisms might be related to immune response induced by CD4(+) and CD8(+) T cells.